The Rhizomatic: A Spatial Form in Contemporary Romanian Poetry - Marius Conkan (Metacritic Journal for Comparative Studies and Theory, 2022)
Using geocritical methods and exploring the spatiality of texts, this study aims to demonstrate that the rhizomatic, the well-known Deleuzian concept, constitutes one of the spatial forms in contemporary Romanian poetry. In this sense, rhizomatic poetics transgress unitary semantics through interferences, disorders and (constantly rearranged) connections of forms and images to ultimately signal new perceptions of reality. As global meanings are pulverized, within some networks that capitalize mainly on the trace and the semantic transgressivity, these poetics end up generating a continuous reassembly of real elements, akin to a system which, through juxtaposition, multiplicity and nomadism, creates its own formal and affective space.